2018
DOI: 10.1074/jbc.ra118.004363
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of cysteine 117 stimulates constitutive activation of the type Iα cGMP-dependent protein kinase

Abstract: The type I cGMP-dependent protein kinase (PKG I) is an essential regulator of vascular tone. It has been demonstrated that the type Iα isoform can be constitutively activated by oxidizing conditions. However, the amino acid residues implicated in this phenomenon are not fully elucidated. To investigate the molecular basis for this mechanism, we studied the effects of oxidation using recombinant WT, truncated, and mutant constructs of PKG I. Using an assay, we observed that oxidation with hydrogen peroxide (HO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…C195 was also shown to adduct the electrophile 8-nitro-cGMP, with this S-guanylation modification leading to persistent activation of the kinase 35 . Hyperoxidation of C117 has been implicated as a mechanism of PKG1α activation by H 2 O 2 , 36 whilst activation by this oxidant was not observed by others 32 . In summary, the redox control of PKG1α is complex, with our understanding continuing to evolve as contemporary studies on the subject emerge.…”
Section: Discussionmentioning
confidence: 99%
“…C195 was also shown to adduct the electrophile 8-nitro-cGMP, with this S-guanylation modification leading to persistent activation of the kinase 35 . Hyperoxidation of C117 has been implicated as a mechanism of PKG1α activation by H 2 O 2 , 36 whilst activation by this oxidant was not observed by others 32 . In summary, the redox control of PKG1α is complex, with our understanding continuing to evolve as contemporary studies on the subject emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Data from an in vitro assay suggest that constitutive activation of PKG-Iα is not mediated via Cys42, but rather through oxyacid formation at Cys117. This mechanism could be particularly relevant to PKG anchored near hydrogen peroxide sources or under pathophysiological conditions associated with high intracellular concentrations of hydrogen peroxide (Sheehe et al 2018).…”
Section: Pgc Structure and Functionmentioning
confidence: 99%
“…Vasodilation by cis-WOOH ultimately derives from the oxidation of Cys 42 in PKG1α. However, Cys 42 might not be the only cysteine residue that can be oxidized to activate the enzyme; Cys 117 seems to be another 12 . The effects of the Cys 42 mutation that Stanley et al used to prevent PKG1α dimerization are also controversial.…”
Section: Fresh Twist In a Biochemical Whodunnitmentioning
confidence: 99%
“…The effects of the Cys 42 mutation that Stanley et al used to prevent PKG1α dimerization are also controversial. Some studies 12,13 have found that it might depress cGMP-stimulated PKG1α activity. Furthermore, PKG1α dimerization triggered by Cys 42 oxidation occurs in the hearts of mice stressed by high blood pressure (pressure overload), yet its prevention in mice with the Cys 42 mutation enhances PKG1αmediated protection against such stress 14 -not by altering PKG1α activation, but by changing the intracellular localization of that enzyme and therefore its interactions with other proteins.…”
Section: Fresh Twist In a Biochemical Whodunnitmentioning
confidence: 99%
See 1 more Smart Citation